THU0202 Five-Year Safety and Efficacy of Golimumab in Patients with Active Rheumatoid Arthritis Despite Previous Anti-Tumor Necrosis Factor Therapy: Final Study Results of the Phase 3, Randomized, Placebo-Controlled Go-After Trial. (23rd January 2014) - Smolen, J. S.; Kay, J.; Landewé, R.; Matteson, E. L.; Gaylis, N.; Wollenhaupt, J.; Murphy, F. T.; Han, C.; Gathany, T.; Xu, S.; Zhou, Y.; Hsia, E. C.; et al.
Abstract : Background: GO-AFTER was the first multicenter, randomized, placebo (PBO)-controlled trial of the safety/efficacy of an anti-TNFα agent, GLM, in pts with active RA despite prior anti-TNFα therapy. Objectives: Final safety/efficacy results through 5yrs are reported. Methods: Pts were randomized (1:1:1) to PBO, GLM 50mg, or GLM 100mg q4w. At wk16, pts with inadequate treatment response entered double-blind early escape: PBO to GLM 50mg or GLM 50mg to 100mg. At wk24 (start of long-term extension), pts still receiving PBO switched to GLM 50mg, all other pts continued current treatment. After the last pt completed the wk24 visit, unblinding occurred, and a one-time GLM dose increase (50 to 100mg) or decrease (100 to 50mg) was permitted at investigator's discretion. The last GLM injection was at wk252. Observed efficacy results (ACR20/50/70, DAS28-CRP, CDAI) by randomized treatment group and cumulative safety data are reported through wks 256 and 268, respectively. Efficacy data from 1 site (16 pts) were excluded (protocol violations). Results: 461 pts were randomized, and 459 received study agent; 183 pts continued treatment through wk252, and 276 pts withdrew (86 for AE, 107 for lack of efficacy, 9 lost to follow-up, 69 for other reasons, 5 deaths). 178 completed the safety follow-up through wk268. Efficacy results are shown in the table. Of pts with available data at wk256, 60.3% had an ACR20, 42.3% had an ACR50, 21.7% had an ACR70, 84.3% had DAS28-CRP EULAR response, 29.0% had DAS28-CRP <2.6, and 16.0% had CDAI≤2.8. The most common AEs were upper respiratory tract infection(27.1%), sinusitis(17.1%), and nasopharyngitis(16.9%). Through wk268, 151/431 pts had an SAE, with similar rates among dose groups (50mg only, 50 and 100mg, 100mg only) Rates of serious infections, malignancies, and death were 13.9%, 4.6%, and 2.1%, respectively. 12.3% of pts had ≥1 injection-site reaction. Of 388 pts with available samples, 31 (8.0%) tested positive for antibodies to GLM. Conclusions: GLM efficacy was maintained through 5yrs among pts with refractory RA who continued treatment. The long-term safety of GLM is consistent with other anti-TNFα agents. Disclosure of Interest: J. Smolen Grant/research support from: Janssen R&D, LLC, J. Kay Grant/research support from: Janssen R&D, LLC, R. Landewé Grant/research support from: Janssen R&D, LLC, E. Matteson Grant/research support from: Janssen R&D, LLC, N. Gaylis Grant/research support from: Janssen R&D, LLC, J. Wollenhaupt Grant/research support from: Janssen R&D, LLC, F. Murphy Grant/research support from: Janssen R&D, LLC, C. Han Shareholder of: Johnson & Johnson, Employee of: Janssen Global Services, LLC, T. Gathany Shareholder of: Johnson & Johnson, Employee of: Janssen Global Services, LLC, S. Xu Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, Y. Zhou Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, E. Hsia Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, M. Doyle Employee of: Janssen R&D, LLC